My Contribution to BulgarianScienceProblems in 2013 [In Bulgarian] - B.V. Toshev (University of Sofia, 2014)
Bulgarianscienceproblems is the only e-mail discussion list, located at yahoogroups.com, moderated by Dr. Lazarin Lazarov, and dealing with the problems of the Bulgarian science and higher education. Its subscribers are currently 5194. This paper lists partly my contribution to the public discussion of the actual situations and challenges of the Bulgarian science in 2013. University/science policy and management and the problems with the failure of the Bulgarian Science Fund are among the main topics considered and discussed.